Promoting Food Security following the 2010 Pakistan Floods and Insights from South Asian Experience - Dorosh, Paul (2011)
Paul Dorosh International Food Policy Research Institute Sohail J. Malik Innovative Development Strategies, Ltd. IFPRI Seminar Jakarta, Indonesia